Influencia de las academias de conducción en el comportamiento de los ciudadanos al momento de conducir por las vías de Bogotá (2013)
The Automobile Education Centers are an important object of study, and in 2012 a large number of these were detected that worked without the basic requirements for the provision of their service established by the Ministry of Transport and the Ministry of Justice in Resolution 3245 of 2009 and Decree 1500 of 2009. From this situation, there is great interest in identifying which are the different causes as a consequence that revolve around it. A situation that is experienced on a daily basis through the Bogota roads and that is possibly influenced by the behavior of drivers at the time of transit is the high congestion and the number of collisions seen on the roads. For this reason we also seek to discover what is the most relevant factor that influences the behavior of drivers. The purpose of this study is to determine the degree of influence that the driving academies or also known as Automotive Education Centers have on the knowledge and behavior of drivers. Additionally, as it is reflected the intervention of the different entities that legislate and promote the good behavior of the drivers at the moment of transit through the Bogota roads Tags from this library: No tags from this library for this title.